1990
DOI: 10.1111/j.1439-0523.1990.tb00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of Isozyme Marker Loci Amongst Androgenetic Plants of Lolium perenne L.

Abstract: lhe segregaiion ol isozyme markers has been examined in lhe ,t;reen and alliino andt-ogenelie progenies ot ivvo plants ol Lolium perenne. Overall the pooled data tor tbe loei P(JI/2 atid G'O7'/2 iloes not deviate Irom expeetation, but there is eonsiderahle heterogeneity between t.unihes and between green ami albino plains, S[iecilie alieles predominate in the diltereni progenv sets, Ihe results mav' be accounted lor by possible linked loci allecting anther culture response or ol linked lethal i^enes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…This type of segregation has also been reported in the DH populations of many crops including Lolium perenne (Hayward et al, 1990), barley (Powell et al, 1986;Thompson et al, 1991), and rice (Guiderdoni et al, 1989). One Table 3.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This type of segregation has also been reported in the DH populations of many crops including Lolium perenne (Hayward et al, 1990), barley (Powell et al, 1986;Thompson et al, 1991), and rice (Guiderdoni et al, 1989). One Table 3.…”
Section: Discussionmentioning
confidence: 90%
“…Alternatively, it is possible that there is selection among the plantlets themselves. In a study Hayward et al (1990) indicated that a genetic component is responsible for disturbed segregations in Lolium. They explained the allele in excess as being linked to the viability genes affecting the generating ability and described them as lethal genes which usually occur in high frequency in naturally out-breeding species.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, segregation distortion due to in vitro androgenesis, resulting in higher allele frequencies of the donor most amenable to tissue culture, can thus be avoided [29,[87][88][89][90][91] [92]. Selection could be performed on the vigorous F 1 hybrids prior to inflorescence harvest and the subsequent recovery of 1-5 DHs per plant [93].…”
Section: Future Applications Of Haploid and Doubled Haploid Techniquementioning
confidence: 99%
“…The same principle can be used to test whether the segregations observed in haploid progenies derived from heterozygotes at marker loci, segregate according to the expected 1:1 ratio. Orton and Browers (1985) in Brassica aleracea, and Hayward et a/. (1990) in Lalium perenne analysed such segregations at four and two isozyme loci respectively.…”
Section: Applications Of Unmapped Markersmentioning
confidence: 99%